Konstitusionalitas Hak Masyarakat Hukum Adat dalam Mengelola Hutan Adat: Fakta Empiris Legalisasi Perizinan - Wahyu Nugroho (The Constitutional Court of the Republic of Indonesia, 2014)
Green constitution placed Indonesia as a country that has a constitutional juridical consequences constitution in 1945 to apply the principles of ecocracy, that is any wisdom or development in the field of economy always looking environment in all sectors, including forestry. The study object is the Constitution Court decision No. 35/PUU-X/2012 with indigenous people’s subject who has violated his constitutional rights. The purpose of this study are: first, to examine and analyze the consistency of state authority over the doctrine of welfare state in the management of state forest with indigenous authorities in the indigenous forest management based on socio-legal study of the Constitutional Court’s decision, and second, guarantees and analyze the implementation of the principles ecocracy over strengthening the constitutional rights of indigenous people as a living law in the management of indigenous forest, as a logical consequence of Indonesia adherents of democracy based on the environment and green constitution. The author uses a methodology based on assessment of the Constitutional Court decision, by examining the socio- legal aspects of this decision. The results of this study revealed that first, there is a relationship between the state is the state forest, and the state is customary forests. To the state forest, the state has full authority to organize and decide the inventory, allocation, utilization, management, and legal relations that occur in the forest region of the country. The indigenous forests, state authority is limited extent authorized content covered in indigenous forest. Indigenous forest management rights of indigenous communities, but if the development of indigenous communities in question no longer exists, then the rights of indigenous forest management falls to the Government. Second, implementation of national and regional development has always prioritized economic element or in the context of regional autonomy prefers the original income, regardless of environmental democracy based on sustainable development and environmentally.